Chemical and Mechanical Properties Studies of Chinese Linen Flax and Its Composites. Issue 5 (June 2013) - Huo, Shanshan; Ulven, Chad A.; Wang, Haoran; Wang, Xinnan
To improve the mechanical performance of flax polymer composites, different surface modifications on flax fibres have been investigated by many researchers. In this study, the effects of alkaline treatment on the properties of Chinese linen flax were evaluated by different chemical and mechanical test techniques. Chemical detergents, stains and FTIR were used to investigate the chemical constituent changes in the Chinese linen flax. Moreover, the elastic properties of untreated and treated flax fibres were evaluated using a single fibre bundle tensile test. The elastic properties of their composites were accessed also using tensile tests. In addition, the theoretical elastic properties of alkaline treated flax were calculated using Halpin-Tsai equations. The theoretical elastic properties of flax/vinyl ester composites were also obtained to compare against the experimental results. An optimal/ultimate elastic modulus of flax/vinyl ester composites was predicted.